Eat prey love - 524988 Sparks, Kerrelyn (Kuala Lumpur : MPH, 2010)
Carlos Panterra is looking for a mate, a woman who will love and care for the young orphans he's recently taken under his wing (or paw, as the case may be). When the shape shifter spies the beautiful Caitlyn, it's like sunshine amidst the darkness. At last, he's found the perfect woman, except . .Caityn Whelan is mortal. Worse, her father is the head of a CIA agency bent on hunting the undead. Still, Caitlyn knows that Carlos is the man for her, shape shifter or not. So she jumps at the chance when her sister offers her a job to work with him, determined to show Carlos their attraction is more than just animal magnetism. But danger lurks in the night, and their unleashed, untamed passion might just get them both killed ...